Tindak Tutur Asertif Pada Interaksi Jual Beli Di Pasar Tradisional Jonggoa Kabupaten Takalar - Ratnasari, Desi; Amir, Johar; M., Asia (SOCIETIES: Journal of Social Sciences and Humanities, 2023)
Abstract. The purpose of this study is to describe the form of speech acts and assertive speech act strategies in buying and selling interactions in the Jonggoa traditional market, Takalar district. This research is based on the theory discussed by Searle (In Leech, 1993). This type of research is qualitative descriptive research. The method used is the collection of research data is recording, see freely involved competent, and recording. Data analysis in this study begins with describing the data in the form of recorded conversation data in the field, the next process is identifying the data, and reducing words. The validity of the data was obtained from the triangulation process  using  the  technique  of  triangulation  of  data sources, observers and theories. The results of this study indicate that speech in the interaction of sellers and buyers acquires six forms of assertive speech acts, namely telling, suggesting, declaring, boasting, complaining, and demonstrating and There are four functions of speech acts, namely competitive, agreeable, cooperative, contradictory. Keywords: Assertive, Forms of Speech Acts,